2019
DOI: 10.3390/su11236640
|View full text |Cite
|
Sign up to set email alerts
|

Search for Measure of the Value of Baltic Sustainability Development: A Meta-Review

Abstract: The purpose of the study is to identify a sustainability development measure. The United Nations announced 17 development objectives in Agenda 2030. This research attempts to identify a measurement which captures all of the UN objectives. It uses the Baltic Sea Region as a natural laboratory for the sustainability discussion. This paper provides an analysis of a sample from the population of 159 research papers, published between 1990 and 2019. With the application of citation count regression, the population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…According to the author's knowledge, the citation count regression has not been used to verify the research gap [37,56] in previous publications. It has been used primarily to limit the population of articles to perform a descriptive review of the literature.…”
Section: Appendix A2 Outline Of the Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the author's knowledge, the citation count regression has not been used to verify the research gap [37,56] in previous publications. It has been used primarily to limit the population of articles to perform a descriptive review of the literature.…”
Section: Appendix A2 Outline Of the Methodsmentioning
confidence: 99%
“…That is, instead of indicating a single value (for business accounting purposes), it would indicate the value of the cost (or profit) of such a transaction for the human environment. By adding a second dimension, we complement the financial information with environmental impacts at each economic transaction level, allowing this system to inherit all aggregates used from accounting equipment, such as financial statements, taxes, public statistics, and particularly gross domestic product [37], national accounts, etc. This results in the transfer of aggregated information for the decision-maker at any organizational level, from the operational manager through to management, owner, state, and local government bodies to the national and international level.…”
Section: Model Conceptmentioning
confidence: 99%
“…To understand the capillarity of the research on the 2030 Agenda, a first step is to take a look to systematic reviews and bibliometric analyses in the topic. In our research, we have identified 27 reviews so far, where the authors focus on studies of the implementation and the achievement of the SDGs (Barrantes Briceño and Almada Santos, 2019; Guha and Chakrabarti, 2019; Gusmão Caiado et al, 2018; Hristov and Chirico, 2019; Khan et al, 2019; Maroyi, 2018; Merino‐Saum et al, 2018; Omer and Noguchi, 2020; Schiappacasse and Müller, 2018; Zhang et al, 2019), on specific topics and collectives within the Agenda (Baum et al, 2016; Del Pino et al, 2019; Giné‐Garriga et al, 2017; Hartmann et al, 2016; Majinge and Mutula, 2018; Mathez‐Stiefel et al, 2017; Matilla et al, 2018; Simcock and Wittich, 2019; Swamy et al, 2018), on traditional fields of knowledge, now reconsidered in the light of the 2030 Agenda (Elfert, 2019; Rodrigues and Franco, 2019; Storey et al, 2017), and even on contributions to the field of knowledge from researchers in specific regions or countries (Körfgen et al, 2018; Staszkiewicz, 2019).…”
Section: The 2030 Agenda For Sustainable Developmentmentioning
confidence: 99%
“…The Baltic Sea region is very important for shipping; therefore, the main aim of our research is to investigate the competitive environment of the Baltic Sea region. Baltic Sea region is a natural laboratory for research on sustainable development [1], especially on economic sustainability. Ports located in the region play a major role in the sustainability of countries, but at the same time face many risks that need to be explored and addressed.…”
Section: Introductionmentioning
confidence: 99%